TUGAS DAN WEWENANG DINAS KEBERSIHAN DAN PERTAMANAN KOTA SEMARANG DALAM UPAYA PELAKSANAAN “WAKTUNYA SEMARANG SETARA” - Vidi Hasiholan Simanjuntak, Amiek Soemarmi, Retno Saraswati (Diponegoro Law Journal, 2012)
The implementation of regional autonomy in accordance with Law No. 32/2004 had many changes, many local communities have gained a little experience of organizing Local Government (LG) system is a new closer. The delivery of government affairs of the central government to the regions was intact in the sense of starting from planning, implementation, and evaluation of all delegated to the regions. In addition, the delivery of government affairs also coupled with the delivery of funding that is encapsulated in the concept of financial balance between central and local   Based on extensive and real autonomy to local governments and municipalities, each local government is required to find and develop core strength by the potential of each area. The discovery core strength is very important because it will be a mainstay and major capital to develop the area in question.   It is also of course made ​​by the Regional Government of Semarang in the framework of regional autonomy, realizing the vision and mission of Semarang City Government with the title " Waktunya Semarang Setara ". Department of Hygiene and Gardener is one of the local agencies that have a role in implementing the tasks that are required and function effectively as possible. Through local agencies as implementing autonomy, local governments are expected vision and mission can be accomplished with either.